COPING WITH THE CHILD OF ACUTE PROMYELOCYTIC LEUKEMIA IN NICK CASSAVETES' MY SISTER'S KEEPER (2009): AN INDIVIDUAL PSYCHOLOGICAL PERSPECTIVE - ANWAR , RITA KUSUMADEWI (2011)
This study is aimed at coping with the child of Acute Promyelocytic Leukemia (APL) in Nick Cassavetes' My Sister's Keeper movie by using Individual Psychological Perspective. It is done by establishing two objectives: the first is analyzing the movie based on its structural elements and the second is analyzing the movie based on the Individual Psychological Perspective. This research is qualitative research. Type of data of the study is text and image taken from two data sources: primary and secondary. The primary data source is the My Sister's Keeper movie directed by Nick Cassavetes released in 2009. While the secondary data sources are other materials taken from books, journals, and internet related to the study. Both data are collected through library research and analyzed by descriptive analysis. The study comes to the following conclusions. Firstly, based on the structural analysis, it is apparent that in this movie, Nick Cassavetes as the director conveys a moral message that "A mother tends to do anything to save the life of her child". It shows that the characters and characterization, plot, setting, point of view, theme, mise en scene, cinematography, sound, editing and casting are related to each other and form the unity into a good quality of movie. Secondly, based on the individual psychological analysis, it is evident that in My Sister's Keeper movie, the director illustrates a psychological phenomenon in which a mother makes every attempt to save her child.